Nutrition security in Tanzania. - Schmidt, Verena (Diplomica Verlag, 2014)
Particularly in developing countries nearly one billion people are effected by nutrition insecurity in form of under- or malnutrition (FAO 2010, p. 1). Merely by the expression of vitamin A-deficiency an estimate of up to 500,000 children go blind worldwide every year (WHO 2011). This survey deals with a solution approach in form of the contribution made by the orange-fleshed sweet potato (OFSP) and its afford towards nutrition security in rural areas of Mwanza, Tanzania. With help of the partner organization TAHEA, a retrospective population-based study of the nutritional status of rural popu.